2012
DOI: 10.1016/j.jacc.2012.07.042
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Circulating Osteogenic Progenitor Cells in Calcific Aortic Stenosis

Abstract: Objectives The purpose of this study was to determine the role of circulating endothelial progenitor cells with osteoblastic phenotype (EPC-OCN) in human aortic valve calcification (AVC). Background Recent evidence suggests that rather than passive mineralization, AVC is an active atherosclerotic process with an osteoblastic component resembling coronary calcification. We have recently identified circulating EPCs with osteogenic properties carrying both endothelial progenitor (CD34, KDR) and osteoblastic (os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 26 publications
4
54
0
Order By: Relevance
“…Moreover, EPCs that express OCN have been found in greater numbers in calcified aortic valve tissue (17). In our study, we also obtained OCN ϩ EPCs when we cultured EPCs from healthy donors with MPs derived from CKD patients, a finding that reinforces the potentially dominant role played by MPs in the development of VC.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, EPCs that express OCN have been found in greater numbers in calcified aortic valve tissue (17). In our study, we also obtained OCN ϩ EPCs when we cultured EPCs from healthy donors with MPs derived from CKD patients, a finding that reinforces the potentially dominant role played by MPs in the development of VC.…”
Section: Discussionsupporting
confidence: 73%
“…Calcification in these tissues follows the accumulation of macrophages, and its final stage is accompanied by the induction during inflammation [14]. Importantly, a new concept suggesting that progenitor cells circulating in the blood under certain conditions can exhibit their osteogenic potential and promote intimal [21] and valvular calcification [22] has recently emerged. It was shown that with increasing progression of aortic valve stenosis, the number of circulating osteocalcin-positive endothelial progenitor cells (CD34 + / OCN +) increased with their subsequent accumulation in the calcified aortic valve tissue [22].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a new concept suggesting that progenitor cells circulating in the blood under certain conditions can exhibit their osteogenic potential and promote intimal [21] and valvular calcification [22] has recently emerged. It was shown that with increasing progression of aortic valve stenosis, the number of circulating osteocalcin-positive endothelial progenitor cells (CD34 + / OCN +) increased with their subsequent accumulation in the calcified aortic valve tissue [22]. Thus, this cascade results in the deposition of calcium, primarily in the zones with critical stress [14].…”
Section: Discussionmentioning
confidence: 99%
“…Osteogenic endothelial progenitor (EP) cells, such as vascular endothelial growth factor receptor-2/CD34-positive cells, contribute to aortic valve calcification in atherosclerosis patients [9][10][11]. Furthermore, two recent studies reported that aortic valve calcification is associated with ectopic ossification induced by various bone marrow-derived circulating osteogenic progenitor (COP) cells, such as type I collagen/CD45-positive and/or osteocalcin/CD45-positive cells [12,13].…”
Section: Introductionmentioning
confidence: 99%